2022
DOI: 10.1155/2022/5423694
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Survival-Related Genes in Acute Myeloid Leukemia (AML) Based on Cytogenetically Normal AML Samples Using Weighted Gene Coexpression Network Analysis

Abstract: The prognosis of acute myeloid leukemia (AML) remains a challenge. In this study, we applied the weighted gene coexpression network analysis (WGCNA) to find survival-specific genes in AML based on 42 adult CN-AML samples from The Cancer Genome Atlas (TCGA) database. Eighteen hub genes (ABCA13, ANXA3, ARG1, BTNL8, C11orf42, CEACAM1, CEACAM3, CHI3L1, CRISP2, CYP4F3, GPR84, HP, LTF, MMP8, OLR1, PADI2, RGL4, and RILPL1) were found to be related to AML patient survival time. We then compared the hub gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Network analysis of various molecular and regulatory factors [49,50] is a strong and widely used approach for exploring the underlying mechanisms of any disease. It has not only been used in AML research [51][52][53] but also for several other diseases and physiological conditions [54][55][56]. In the current study, we constructed protein-protein interaction network and revealed the close relationships among the m5C regulators.…”
Section: Discussionmentioning
confidence: 90%
“…Network analysis of various molecular and regulatory factors [49,50] is a strong and widely used approach for exploring the underlying mechanisms of any disease. It has not only been used in AML research [51][52][53] but also for several other diseases and physiological conditions [54][55][56]. In the current study, we constructed protein-protein interaction network and revealed the close relationships among the m5C regulators.…”
Section: Discussionmentioning
confidence: 90%
“…First, transferrin receptor levels possibly reflect differences in iron metabolism that are important for chemosensitivity [94,95], extracellular mediator release and non-relapse survival after intensive therapy [96][97][98][99]. Second, Chitinase 3-like level is associated with survival for AML patients receiving intensive therapy [100,101]; cellular expression or systemic levels of the soluble form may function as markers of susceptibility to V-ATPase inhibition. Third, the secreted protein C type lectin domain containing 11A functions as a hematopoietic growth factor and high expression is associated with prognosis in AML [102,103].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the expression level of GPR84 was significantly related to the survival time of AML patients. 171 , 172 Mechanistically, GPR84 overexpression induces activation of the β-catenin transcriptional cofactors Tcf7l2 and c-Fos as well as genomes associated with Wnt signaling. 173 GPR84 antagonists have been evaluated in clinical trials to treat ulcerative colitis, idiopathic pulmonary fibrosis, and nonalcoholic steatohepatitis.…”
Section: Metabolite Sensing and Epigenetic Regulation Of Fatty Acid M...mentioning
confidence: 99%